Characterization of the standard food and nutritional status of collective drivers of Bauru-SP - Morais, Renato Alves de; Souza, Debora Tarcinalli; Togneri Ferron, Artur Junio [UNESP]; Souza, Carolina Tarcinalli; Francisqueti, Fabiane Valentini (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
There is a growing rate of chronic diseases worldwide, which carries high financial cost for the country and damage in the population's life quality. Urban public bus drivers are a risk class because of sedentary work, stressful conditions and often poor diet, which favors obesity and related comorbidities. So, this study aimed to characterize the nutritional status and dietary pattern of urban public bus drivers in Bauru-SP. Cross sectional study, that evaluated individualized nutritional assessment, socio-economic information and food habits-24-hour recordatory and food frequency questionnaire. The data showed that most drivers is overweight or obese, excessive body fat and increased waist circumference, which represented increased cardiovascular risk. Eating habits showed higher consumption of sugars, saturated fats, cholesterol and sodium and lower intake of fruits and vegetables. Thus, it is possible to conclude that the study population shows higher risk for comorbidities related-obesity, requiring correct nutritional intervention.
Keywords: Drivers; Nutritional Status; Eating Habits